Relevansi Hadis Tarbawi Tentang Pendidikan Anak Dalam Shahih Bukhari Muslim Terhadap Pendidikan Anak Di Era Modern - M Aditya Nasution; Danny Abrianto (Yayasan Rahmat Islamiyah, 2025)
This study aims to explore the relevance of the hadith tarbawi about children's education contained in the Sahih Bukhari and Muslim in the context of children's education in the modern era. Children's education in Islam has a strong foundation, which not only includes academic aspects, but also character and moral education. The study of this study is related to the hadith tarbawi about children's education in the Sahih Bukhari Muslim towards children's education in the modern era. The method that will be used to strengthen the application and approach of the hadith tarbawi about children's education in the Sahih Bukhari Muslim towards children's education in the modern era is a qualitative research method that can be interpreted as literature or library research which is expected to provide new insights and practical recommendations for parents, educators, government, and society in educating children in the midst of the challenges of the times. This research can also provide a positive contribution to the development of children's education, as well as increase public awareness of the importance of character and moral education based on Islamic teachings in forming a quality generation